Physical Condition Analysis of Junior High School Volleyball Players: A Study on the Extracurricular of Junior High School 3 Semarang - Ahmad Kholik Husain; Rumini (Journal of Physical Education Health and Sport, 2025)
Physical conditioning is an essential of volleyball play, involving strenght, speed, endurance, agility coordination and flexibility. But the gym program of schools extracuricular is crushed in a below priority with respect to technical training. This research aimed to describe the reality of physical fitness in general on volleyball extracuricular participants at Junior High School 3 Semarang objectively, considering gender category. The purpose of this study was to determine the global physical fitness profile of students who participated in extracurricular volleyball and contrast athletic performance between male and female participants. This research was quantitative in nature with 62 students selected through total sampling technique. Physical accomplishment was measured in muscle strength, endurance, power, speed,flexibility,agility, coordination and balance. The raw scores of each subscale were transformed into T-scores and classified into five skill levels based on predefined normative criteria. The findings indicate that subjects had low physical fitness levels. For the women, 40% achieved a moderate level and 24% an inferior level; 20 and 8% reached the high and very high level respectively and only 8% were found to be at the very poor level. The trends for men were along the same line, as 34.2% reached to poor and 31.5% hit moderate weight classes. In contrast, 26.4% of them accomplished the High level while at the Very high level 7.9% and nobody attained to Very poor level. Extracuricular participants physical conditioning status is between fair to poor, suggest a more structured, comprehensive training program focusing on both physical and technical development in order to excel in maximal performance of vollyball.